2017
DOI: 10.1002/2017gl076261
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Mechanisms Causing Rapid Drought Cessation in the Southeastern United States

Abstract: The synoptic processes that end droughts are poorly understood, yet have significant climatological implications. Here we examined the spatiotemporal patterns of rapid drought cessation (RDC) in the southeastern United States during the1979-2013 warm season (April-November) for three storm types: Frontal, Tropical, and Air mass. We defined RDC as a 1 month shift in soil moisture sufficient to alleviate an existing drought. We found that 73% of all warm-season droughts were ended by RDC events and the three sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…were nearly identical to those of non-tropical precipitation days ( Figures S3 and 3c and 3d). This is consistent with the dominance of frontal storm types in the fall precipitation climatology (Kunkel, Easterling, et al, 2012) and rapid drought cessation from high-intensity precipitation events (Maxwell et al, 2017) in the southeastern United States. Despite the fact that fall is the peak tropical cyclone season in the SE-Gulf, tropical cyclones did not dominate the fall precipitation record.…”
Section: Geophysical Research Letterssupporting
confidence: 84%
“…were nearly identical to those of non-tropical precipitation days ( Figures S3 and 3c and 3d). This is consistent with the dominance of frontal storm types in the fall precipitation climatology (Kunkel, Easterling, et al, 2012) and rapid drought cessation from high-intensity precipitation events (Maxwell et al, 2017) in the southeastern United States. Despite the fact that fall is the peak tropical cyclone season in the SE-Gulf, tropical cyclones did not dominate the fall precipitation record.…”
Section: Geophysical Research Letterssupporting
confidence: 84%
“…When these streams interact with the coastal topography of the U.S. West Coast they can cause extreme high precipitation, sometimes so high that persistent droughts can be terminated in a few weather events (see, e.g., Dettinger 2013Dettinger , 2016. In addition there has been work on how tropical cyclones can contribute to drought relief or termination in the southeast United States (e.g., Kam et al 2013;Maxwell et al 2013). In more general prior work on DO&T, Karl et al (1987) noted that the probability of amelioration or termination of a drought depends on the mean annual cycle of precipitation, being highest in wet seasons that have the possibility of extreme wet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Dettinger (2013) argued that drought onsets are slower than terminations because negative precipitation anomalies cannot exceed the negative of the climatological precipitation, but positive anomalies easily can. However, Maxwell et al (2017) specifically studied rapid drought terminations at the local scale across the southeast United States. For this region they found that rapid termination was most likely in summer and fall with fronts and tropical cyclones the two most likely causes and atmospheric rivers responsible for considerably fewer terminations.…”
Section: Introductionmentioning
confidence: 99%
“…TCs are characterized by high winds, coastal storm surge, and extremely intense precipitation that can extend far inland after a TC makes landfall and weakens. TC‐related extreme precipitation frequently contributes to drought demise, and the impacts have been discussed using both observed and model data (Kam et al, ; Lam et al, ; Maxwell et al, ; Maxwell et al, ; Maxwell et al, ; Misra & Bastola, ). In the Northeast United States, two thirds of the extremes in precipitation during the hurricane season have been related to TCs (Barlow, ), and the affected region from one TC often spans several hundred kilometers.…”
Section: Introductionmentioning
confidence: 99%